The medieval stockfish trade: a maritime perspective from northern Norway - Wickler, Stephen (Âncora Editora, 2021)
Life in northern Norway has been dependent on the sea and marine resources since initial settlement following the retreating ice at least 11,500 years ago. Small islands have played a significant role for maritime communities since the Mesolithic when occupation of offshore islands reflected the maritime orientation of hunter‑gatherer settlement. Although settlement along the coast, including coastal islands, in northern Norway has been the subject of extensive archaeological interest, archaeologists have generally under communicated the importance of smaller islands as central nodes in coastal communication, contact and exchange binding the inhabitants of northern Norway to one another since the Stone Age. This is paralleled by the present‑day situation in which small islands that were formerly socio‑economic midpoints have been transformed into depopulated remote entities on the margins of society over the past century. The following overview of archaeological evidence for the development of maritime communities in Arctic Norway and their linkages to the medieval stockfish trade focuses to a large extent on the central importance of islands where stockfish was produced for export.